2020
DOI: 10.26443/crae.v47i1.91
|View full text |Cite
|
Sign up to set email alerts
|

“Illustrating” the Role of the Expressive Arts Among Children and Youth with Cystic Fibrosis: A Narrative Review

Abstract: In this paper, the authors conduct a narrative review of the literature to explore the role of the expressive arts in the lives of children and youth with cystic fibrosis (CF). While most research designs in this review were case studies, researchers used a variety of art forms in their studies, including poetry, photography and drawing. Our findings reveal that researchers used the expressive arts to understand and address the psychosocial states, social health, physical health, and coping patterns of childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The ability of expressive arts therapy, which includes art therapy, to promote people's mental health and wellbeing has been acknowledged. Studies have shown how art therapy can be used in a variety of contexts, including the treatment of eating disorders (Bucharová et al, 2020), the treatment of trauma (Fernández-Cao et al, 2020), and the support of people who have cystic fibrosis (Posa & Moola, 2020). Professionals have employed expressive arts, such as visual arts, music, dance, and drama, to facilitate self-expression, emotional regulation, and experience exploration with youth in schools (Degges-White, 2019).…”
Section: Art Therapy: Abilities and Impactsmentioning
confidence: 99%
“…The ability of expressive arts therapy, which includes art therapy, to promote people's mental health and wellbeing has been acknowledged. Studies have shown how art therapy can be used in a variety of contexts, including the treatment of eating disorders (Bucharová et al, 2020), the treatment of trauma (Fernández-Cao et al, 2020), and the support of people who have cystic fibrosis (Posa & Moola, 2020). Professionals have employed expressive arts, such as visual arts, music, dance, and drama, to facilitate self-expression, emotional regulation, and experience exploration with youth in schools (Degges-White, 2019).…”
Section: Art Therapy: Abilities and Impactsmentioning
confidence: 99%